2018
DOI: 10.1177/1461348418756022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a group of quasi-zero stiffness vibration isolators with slightly different parameters

Abstract: This article is devoted to finding solutions of problems of vibration isolators with quasi-zero stiffness from a manufacturing point of view. The following study is appeared after experimental study and manufacturing of preproduction serial of universal isolators of a dome type. An analytical description of some types of vibration isolators with quasi-zero stiffness is briefly observed. The sensitivity of vibration isolators of a dome type is studied. It is proved that vibration isolators with quasi-zero stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The spacing washers height should also be 2f [22]. The static force characteristic of a separate Belleville spring is known to be described by the following nonlinear dependence [21,22]…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The spacing washers height should also be 2f [22]. The static force characteristic of a separate Belleville spring is known to be described by the following nonlinear dependence [21,22]…”
Section: Theorymentioning
confidence: 99%
“…Examples of the two static characteristics obtained from (2) are shown in figure 1a. It is known that The separate Belleville spring dimensions s and f are known to be related both to each other and to the coefficient k, on which the stiffness and the slope angle in the center of the spring static characteristic depend, by the ratio [21,22]:…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al designed a pre-compressed cam-roller mechanism for proposing a QZS torsion vibration isolator [15]. Valeev analyzed the dynamics performance of a group of QZS vibration isolators from the manufacturing perspective, and the analysis results indicated that QZS vibration isolators required high precision at manufacturing [16]. Through imitating both multivertebra structure of bird's neck and gazing stability of head, Deng et al analyzed a multi-layer QZS isolator [17].…”
Section: Introductionmentioning
confidence: 99%
“…This isolator possesses high-static-low-dynamic stiffness so that it can maintain the load-bearing capacity with a small static displacement and achieve a lower natural frequency to enlarge frequency ranges of vibration isolation. But, it should be noted that isolators with QZS are very sensitive facilities and if something occurs to cause deviation of its characteristic parameters (e.g., mismatch of the load and negative stiffness parameters) and/or change in the non-linearity properties of its forces (e.g., destruction of the symmetry), then the isolation performance will change dramatically [19][20][21][22]. This situation is particularly true when the amplitude of excitation is not relatively small, and the isolator is exposed to a sustained excitation.…”
Section: Introductionmentioning
confidence: 99%